2019
DOI: 10.1115/1.4044400
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fidelity Physics-Constrained Neural Network and Its Application in Materials Modeling

Abstract: Training machine learning tools such as neural networks require the availability of sizable data, which can be difficult for engineering and scientific applications where experiments or simulations are expensive. In this work, a novel multi-fidelity physics-constrained neural network is proposed to reduce the required amount of training data, where physical knowledge is applied to constrain neural networks, and multi-fidelity networks are constructed to improve training efficiency. A low-cost low-fidelity phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…We characterize the phenomenon of vanishing task-specific gradients, demonstrate its impact on the accuracy of a learned function approximation, and empirically validate Proposition 2.2.1. For this, we consider a generic neural network with five layers and 64 neurons per layer, tasked with learning a 2D function that contains a wide spectrum of frequencies and unknown coefficients ξ = ( ξ1 , ξ2 , ξ3 , ξ4 ) using Sobolev training with the loss from equation (10). The details of the test problem and the training setup are given in appendix B.…”
Section: Inverse Dirichlet Weighting Avoids Vanishing Task-specific G...mentioning
confidence: 99%
See 1 more Smart Citation
“…We characterize the phenomenon of vanishing task-specific gradients, demonstrate its impact on the accuracy of a learned function approximation, and empirically validate Proposition 2.2.1. For this, we consider a generic neural network with five layers and 64 neurons per layer, tasked with learning a 2D function that contains a wide spectrum of frequencies and unknown coefficients ξ = ( ξ1 , ξ2 , ξ3 , ξ4 ) using Sobolev training with the loss from equation (10). The details of the test problem and the training setup are given in appendix B.…”
Section: Inverse Dirichlet Weighting Avoids Vanishing Task-specific G...mentioning
confidence: 99%
“…The popular physics informed neural networks (PINNs) rely on knowing a differential equation model of the system in order to solve a soft-constrained optimization problem [5,8]. Thanks to their mesh-free character, PINNs can be used for both forward and inverse modeling in domains including material science [9][10][11], fluid dynamics [8,[12][13][14] and turbulence [15,16], biology [17], medicine [18,19],…”
Section: Introductionmentioning
confidence: 99%
“…Physics-informed neural networks have been shown to produce good results for some applications, such as the modelling of materials [26] and high-speed flows [27], but show limitations in their current form that are not yet well understood [28]. For instance, it has been demonstrated that physics-informed models fail to provide good solution approximations for flow in porous media when shocks are introduced [29] and that some LSTM models may not perfectly resolve turbulent conditions [30].…”
Section: Image Super-resolution Applied To Cfdmentioning
confidence: 99%
“…Physics has also been used as a prior in reinforcement learning [222]. As low fidelity MB's capture the general trend and the high fidelity MBs additionally capture intricate local details, a multi-fidelity physics constrained NN was proposed for incorporating linear and nonlinear PDEs [223].…”
Section: Physics Based Regularizationmentioning
confidence: 99%